DAMPAK TERPAAN IKLAN SHOPEE COD TERHADAP MINAT BELI PEREMPUAN - Agung Raharjo; Fajar Kurniawan; Fitriyanto; Faikoh Umairoh; Marulitua A, Bonardo (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2023)
The increasingly rapid advances in technology can be a determining factor in the success of an advertisement in reaching buyers' interest in a particular product. The development of e-commerce with a variety of shopping options makes consumers increasingly intent on buying instantly. Advertising exposure to consumer buying interest is high with several services that e-commerce provides in its sales. This research aims to evaluate whether exposure to the "Shopee COD" version of advertising from Shopee, which is broadcast on television, has an influence on teenage girls' buying interest. The research method used is quantitative descriptive, which explains the causal relationship between two variables. Data was collected through distributing questionnaires to respondents. The results of the research show that there is an influence between exposure to the "Shopee COD" version of Shopee advertising on television on the buying interest of teenage girls in the East Rawasari area.